A comparison between the mechanical properties of the hepatic round ligament and the portal vein: a clinical implication on surgical reconstruction of the portal and superior mesenteric veins. Issue 13 (2nd October 2020) - Zhu, Wentao; Song, Rongqiang; Cao, Xuefeng; Zhou, Lei; Wei, Qiang; Ji, Haibin; Fu, Rongzhan
Abstract: Abdominal malignant tumors originated from cancers, such as vater ampulla carcinoma (VAC) and pancreatic cancer (PC), often invades the portal vein (PV) and the superior mesenteric vein (SMV) upon metastasis. Surgical removal of these tumors leads to sacrifice of parts of these vessels that need to be reconstructed with autograft tissues. Current options for the replacement tissue all have their limitations in certain aspects. Therefore, improved interstitial material for the reconstruction with better tissue compatibility is urgently needed. In the present study, we explored the potential of hepatic round ligament (HRL) as a candidate tissue for the task from the biomechanical point of view. We reveal that HRL and PV share similar geometrical parameters in terms of vascular cavity diameter and wall thickness. In addition, they also have similar elastic properties and tissue flexibility and intensity upon increased cavity pressure. Our study strongly supports HRL as potential replacement tissue for PV reconstruction in term of mechanical properties and encourages further biological studies to be performed on these two tissues for further verification.